Impact of the COVID-19 pandemic on the financial well-being among older adults in Malaysia - Muhammad Amjad Khan; Khor Saw Chin; Charles Ramendran (International Journal of Management, Economics and Social Sciences (IJMESS), 2021)
The purpose of this study was to explore the impact of the COVID-19 pandemic on the financial well-being among older adults in Malaysia. The study was carried out a literature review to evaluate research published in journals and conference proceedings in Malaysia relating to older adults. The study applied personal control theory to evaluate the COVID-19 pandemic's impact on the financial well-being among older adults in Malaysia. The findings of this study demonstrated that older adults lost their source of income during the COVID-19 pandemic that has adversely affected their financial well-being. This study contributes to shape a sustainable society by offering constructive knowledge of the financial well-being of older adults as they were a more vulnerable portion of society in the COVID-19 pandemic. The study concluded that policymakers should develop effective social security policies to absorb financial shocks so that the lifestyles of older adults can be improved.
Keywords: E24; I15; I38; 330; COVID-19; pandemic; older adults; financial well-being; Malaysia